Analisis Tata Cara Klaim Asuransi di Jasa Raharja Atas Pemberian Biaya dan Santunan Kepada Korban Kecelakaan Lalu Lintas (Studi Kasus PT. Jasa Raharja Sumatera Utara Medan) - Siti Nurhaliza Lubis; Rahmi Syahriza (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This researcher analyzes the relationship between inheritance law and PT JasaRaharja, carries out the compensation claim process to victims of traffic accidents, and the factors that hinder claims. This is a qualitative research with applied normative approach. The resource persons consist of 1 party and 2 patients/patient families. And to find out the procedure for the insurance claim for the top raharja service to provide compensation for victims of Medan traffic accidents. Based on the results of this study, it can be said that it is related to the law of the heirs or victims who act as a binder in the data collection relationship in the form of mandatory rights on each party. Compensation claims for victims who are injured in traffic can be filed with the victim's heirs by filling in the compensation application. The factors that hinder claims are that the premium payment is not in accordance with the provisions, and the insurer often delays in reporting claims, and families who will not fulfill the requirements have been determined in filing a claim, and treatment can result in accidents on highway traffic. can do it in the traditional place of the heir, and many do not know the obligation to fulfill the conditions for applying for compensation funds for traffic accidents. The method this researcher has used in the preparation of this article is a qualitative and descriptive method. The informants in the researcher consisted of 1 informant from the North Sumatran Raharja Service Office. The data used is primary data obtained directly through interviews with informants.